Financial Transactions Plan : Temporary Modification of Guidelines for Allocation of Currencies Used for Transfers. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
This paper proposes a temporary modification of the current guidelines for allocation of currencies used for transfers in the Financial Transactions Plan (FTP). This temporary modification is designed to promote fair burden sharing between NAB participants that have bilateral borrowing agreements or note purchase agreements (hereafter referred to as 'bilateral agreements') and participants that do not have such agreements, and would result in a change from the current approach only for those FTP members that are NAB participants. It is proposed that the current guidelines for allocation of currencies used for transfers be reinstated automatically for all FTP members when all pre-NAB bilateral agreements have been terminated and when any imbalances in NAB positions resulting from the folding in of claims under bilateral agreements have been eliminated, or at an earlier date as decided by the Executive Board.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Fund; Holding; NAB Participant; New Arrangement To Borrow; PP; United Arab Emirates